Characterization of ERK2 as a Transcriptional Repressor of Growth Arrest Specific Genes - Athar, Mohammad S. (My University, 2011)
The study of growth arrest specific (GAS) genes is critical for our understanding of quiescence cell states. C/EBP-β is a transcriptional activator which is central to the expression of GAS genes in growth arrested cells. C/EBP-β is involved in the activation of numerous pathways, including mitogenesis, cytokine signaling, stress response, etc. Thus, it requires signaling cues which confer specificity in terms of gene expression.
Here we used the p20K gene in chicken embryonic fibroblasts as a model system to study the control mechanisms of GAS genes. p20K is expressed in conditions such as contact inhibition mediated growth arrest and mild hypoxia. Here we explored the control mechanism mediated by ERK2 at the p20K promoter (QRU), as a mode of regulation which confers C/EBP-β binding specificity.
In this study we demonstrate that ERK2 is recruited to the QRU in proliferative cells, i.e. where p20K is repressed. Using ChIP analysis we show that ERK2 binds directly to the QRU in proliferative cell states, but not in growth arrested cell conditions. Using a similar approach we demonstrate that ERK2 binding to the QRU is lost in states of hypoxia, where p20K is strongly induced. Furthermore, we show that this interaction is specific to ERK2 and is not observed with the related ERK1 kinase. Lastly, we employed transient expression assays to illustrate that ERK2 acts as a transcriptional repressor of the QRU. Through these experiments we have illustrated that ERK2 mediated transcriptional repression is a novel control mechanism at the QRU which skews C/EBP-β mediated signaling networks in proliferating cells.
Keywords: ERK2; p20K; Quiescence; Growth Arrest; C/EBP-B; Transcription; Cell Biology; Cell Biology